ABCD Model Implemented to Underdeveloped Villages in Trenggalek Regency - Didiek Tranggono; Praja Firdaus Nuryananda; Andre Yusuf Trisna Putra (Future Science)
Trenggalek Regency is an area located in the southern part of East Java Province. Due to its geographical position in the south and the lack of transportation facilities, Trenggalek Regency is a developing area with relatively slow progress. There are also still many underdeveloped villages. This research will discuss three underdeveloped or developing villages in Trenggalek. Tegaren village was once a village with IDT status (Inpres Desa Tertinggal), the consequence of which was often to get assistance from the government. Meanwhile, Winong Village is a village that is also included in a backward village. Tasikmadu village in Watulimo District is a prototype of a coastal village that is still classified as being left behind even though it is located in a tourist area. The research we have done is an implementation of the ABCD (Asset Based Community Development) model by Christopher Dureau that focuses on asset utilization. For the implementation of the ABCD method, this research uses a mixed method with interviews, observations, and questionnaires. This research will focus on community development and empowerment in underdeveloped villages of Trenggalek Regency by focusing on village assets. The problem that then arises is that both Tasikmadu, Winong, and Tegaren Villages are typical villages that do not yet have or have not maximized the village assets they have. A preliminary finding by the research team is that the empowerment of underdeveloped rural communities is strongly supported by a strong level of education and institutional leadership system.